STRATEGY FOR ENHANCING THE SUSTAINABILITY OF COMMUNAL SANITATION INFRASTRUCTURE IN MAJALAYA DISTRICT BANDUNG REGENCY (CASE STUDY : CIWALENGKE HAMLET) - Stefani Sembiring, Valeria
The Citarum River, which has a high pollutant load, is used by the residents of Ciwalengke Hamlet for daily activities. One of its uses is in public bath, wash, and toilet activities. The communal sanitation facilities in Ciwalengke Hamlet, located in RW 08 and RW 10, have been in operation for 20 years and are currently in a state of disrepair and neglect. Poor sanitation conditions necessitate an analysis of strategies to enhance the sustainability of the communal sanitation infrastructure in Ciwalengke Hamlet, Majalaya District, Bandung Regency. This study aims to identify the conditions and problems related to the sustainability of sanitation facilities in Ciwalengke Hamlet. The research was conducted using secondary data and primary data in the form of questionnaires, as well as descriptive analysis to evaluate the existing conditions in Ciwalengke Hamlet and a Chi-Square independence test to examine the influence of community willingness to provide land and monthly contributions towards improving sanitation facilities in Ciwalengke Hamlet. The AHP (Analytical Hierarchy Process) method was used to select the appropriate wastewater treatment technology for the sanitation facilities in Ciwalengke Hamlet. The selection criteria included removal efficiency, cost, ease of operation and maintenance, and use of land. Three alternatives were considered: conventional septic tanks, biofiltration, and constructed wetlands, with all three alternatives having high efficiency, easy maintenance, and relatively low operational and maintenance costs. The sustainability improvement of the communal sanitation infrastructure in Ciwalengke Hamlet used SWOT analysis to determine appropriate and suitable strategies. Based on the study results, the existing condition of the sanitation facilities in Ciwalengke Hamlet still does not meet the applicable standards and regulations. Most domestic wastewater is not treated and is discharged directly into the river, while water use in sanitation facilities came from river water. The community believes that the sanitation facilities are very beneficial in their daily lives, and most are willing to contribute to improving the sanitation facilities. However, only a few residents are willing to provide land, while quite a few are willing to contribute monthly fees for the operation and maintenance of sanitation facilities. Land and economic constraints necessitate consideration of land use and cost factors in improving sanitation facilities in Ciwalengke Hamlet. The wastewater treatment technology proposed in this study is biofiltration, based on the analysis results using the AHP method. The proposed sustainability strategy in this study is the WO (Weakness-Opportunity) strategy with key factors including the development of wastewater treatment technology, the formation of a community to manage communal sanitation infrastructures, and public education on sanitation.